Die-attach bonding for high temperature applications using thermal decomposition of copper(II) formate with polyethylene glycol. (June 2020) - Bhogaraju, Sri Krishna; Mokhtari, Omid; Conti, Fosca; Elger, Gordon
Abstract: A copper paste based on commercial available copper(II) formate microparticles and polyethylene glycol as binder has been developed for bonding of semiconductor dies onto substrates below 300 °C. Thermal decomposition of copper(II) formate leads to the formation of copper nanoparticles, which are used to connect the chip electrically and mechanically to the substrate by a sinter process. The binder provides printability of the paste, protects the copper particles from oxidation and supports the formation of fine copper nanoparticles. Shear tests of the sintered interconnects return shear strength values of 60 MPa, offering a promising solution to form pure copper interconnects. Graphical abstract: Image, graphical abstract